2018
DOI: 10.1101/499483
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Urinary biomarkers and cardiovascular outcomes in the UK Biobank: observational and Mendelian randomization analyses

Abstract: BackgroundUrinary biomarkers are associated with hypertension and cardiovascular disease (CVD), but the nature of these associations is incompletely understood. MethodsWe performed multivariable-adjusted regression models to assess associations of urinary sodium-potassium ratio (UNa/UK), and urinary albumin adjusted for creatinine (UAlb/UCr) with cardiovascular risk factors, CVD and type 2 diabetes (T2D) in 478,311 participants of the UK Biobank. Further, we studied above associations separately in men and wom… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 36 publications
0
9
1
Order By: Relevance
“…This cardiac electrical instability associated with sodium excretion is at least in part in line with our results. In another study in the UK Biobank, Zanetti et al [25] found an inverse relationship between the ratio of urinary sodium and urinary potassium (uNA/uK) and AF, which stands somewhat in contrast to our results. However, disturbance in the potassium balance is far more arrhythmogenic than fluctuances in the sodium homeostasis [26], which could explain some of the discrepant results.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This cardiac electrical instability associated with sodium excretion is at least in part in line with our results. In another study in the UK Biobank, Zanetti et al [25] found an inverse relationship between the ratio of urinary sodium and urinary potassium (uNA/uK) and AF, which stands somewhat in contrast to our results. However, disturbance in the potassium balance is far more arrhythmogenic than fluctuances in the sodium homeostasis [26], which could explain some of the discrepant results.…”
Section: Discussioncontrasting
confidence: 99%
“…Even though associated with some biases, we believe that relating urinary spot sample concentrations of sodium to the concentration of urinary creatinine gives a more reliable, concentration‐adjusted estimate than isolated spot measurements of two urinary electrolytes. Interestingly, Zanetti et al [25] found positive effects between raised uNa/uK and increased blood pressure in both, observational analysis and Mendelian randomization studies. Another UK Biobank study [27] reported suggestive causal effects between raised urinary sodium excretion and increased diastolic blood pressure, as well as between raised urinary potassium and lower systolic blood pressure in Mendelian randomization analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosis of T2DM patients was based on the recommendations of American Diabetes Association (16). DN was diagnosed based on GFR level ( < 60 mL / min / 1.73m 2 ) or persistent microalbuminuria ( > 19 μg / mL) in the morning urine of patients (17,18). Demographical data were collected via a structural interview that was conducted during the visit.…”
Section: Subjectsmentioning
confidence: 99%
“…We identified 108 risk factors from the IEU OpenGWAS database for inclusion in our analysis. ( 19 (38); urinary sodium-potassium ratio (39); and waist-to-hip ratio (40).…”
Section: Risk Factor Selectionmentioning
confidence: 99%